Probing gravitational fluctuations in spherically symmetric black holes and extreme mass ratios systems - Lucchini, André Felipe Moraes Luiz [UNESP] (UNESP, 2024)
Einstein’s theory of General Relativity transformed our understanding of gravity by predicting the existence of black holes—astrophysical objects with gravitational fields so strong that not even light can escape. Over time, theoretical developments and astronomical observations have established black holes as key phenomena in modern astrophysics, particularly in the study of Extreme Mass Ratio Inspirals (EMRs), where a supermassive black hole interacts with a much smaller compact object. These systems are vital for testing the predictions of General Relativity, as they generate gravitational waves that encode detailed information about the properties of the black hole and the surrounding spacetime. This master thesis reviews the literature on gravitational perturbations emitted by black holes, examining the emergence of quasi-normal modes (QNMs) and their role in dissipating energy via gravitational waves. Furthermore, it shows the dynamics of radial infall in Schwarzschild black holes and the application of perturbative methods in Kerr spacetime to explore gravitational self-force effects in EMRIs, reviewing into it orbital evolution and dissipative mechanisms.

A teoria da Relatividade Geral de Einstein transformou nossa compreensão da gravidade, prevendo a existência de buracos negros — objetos astrofísicos com campos gravitacionais tão intensos que nem mesmo a luz consegue escapar. Com o tempo, desenvolvimentos teóricos e observações astronômicas estabeleceram buracos negros como fenômenos-chave na astrofísica moderna, particularmente no estudo de Inspirais de Razão de Massa Extrema (EMRIs), onde um buraco negro supermassivo interage com um objeto compacto muito menor. Esses sistemas são vitais para testar as previsões da Relatividade Geral, pois geram ondas gravitacionais que codificam informações detalhadas sobre as propriedades do buraco negro e o espaço-tempo circundante. Esta dissertação de mestrado faz uma revisão bibliográfica das perturbações gravitacionais emitidas por buracos negros, examinando o surgimento de modos quasi-normais (QNMs) e seu papel na dissipação de energia por meio de ondas gravitacionais. Além disso, ele mostra a dinâmica da queda radial em buracos negros de Schwarzschild e a aplicação de métodos perturbativos no espaço-tempo de Kerr para explorar efeitos de self-force gravitacional em EMRIs, revisando sua evolução orbital e seus mecanismos dissipativos.
Explorando flutuações gravitacionais em buracos negros esfericamente simétricos e sistemas de razão de massa extremas
Keywords: black-holes; gravitational perturbation; quasi-normal modes; radial infall; extreme-mass-ratio inspiral; Buracos negros (Astronomia); Perturbação (Astronomia); Ondas gravitacionais; Massa (Física)